(untitled) (Mustansiria Dental Journal, 2018)
Background: The esthetic application of bleaching materials has gained popularity, with consequences for teeth and restorative materials. The purpose of this an in vitro study was to investigate the effect of in-office bleaching agent (38% hydrogen peroxide) on the color change of three composite resins after staining with tea and coffee beverages. Materials and Methods: Sixty disc-shaped samples from three different composite resins (Tetric Ceram, Tetric Flow and Tetric Evo Ceram) were used in this study. The samples of each group were randomly divided into two subgroups according to type of beverages (tea and coffee) used for staining of samples. After staining of composite resins the total color change (ΔE1 ) was calculated using spectrophotometer, then the samples immersed in WHITEsmile® office bleaching agent for 15 min x 3 times with a 7 days interval followed by ΔE2 calculation. Data were subjected to the ANOVA, LSD and student t-test at 0.05 significance level. Results: The results revealed that, there was clinically significant color change ΔE> 3.3 with a statistically highly significant differences (P=0.000) for all the groups. Coffee causes more discoloration than tea. After bleaching, the samples became whiter in color and only appreciable by skillful operator but considered clinically acceptable ΔE1 - ΔE2 < 3.3. Conclusion: Tea and coffee beverages causes discoloration in composite but this effect was depended on the type of beverages and composite resins. The most of color change occurred with Tetric Flow composite resin after immersion in coffee beverage. The bleaching agent (38% hydrogen peroxide) can remove the staining of composite resins and make its color clinically acceptable.